Association between NOTCH3 gene and Parkinson’s disease based on whole-exome sequencing - Zeng, Qian; Pan, Hongxu; Zhao, Yuwen; Wang, Yige; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; Guo, Jifeng (Frontiers in Aging Neuroscience, 2022)
Objective Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary cerebral small vessel disease caused by mutations in the NOTCH3 gene. Previous studies have established a link between NOTCH3 variants and Parkinson’s disease (PD) in terms of neuropathology and clinical characteristics. In this study, we aimed to explore the role of NOTCH3 gene in PD in a large Chinese cohort. Methods A total of 1,917 patients with early-onset or familial PD and 1,652 matched controls were included. All variants were divided into common or rare types by minor allele frequency (MAF) at a threshold of 0.01 (MAF > 0.01 into common variants and others into rare variants). Common variants were subjected to single-variant tests by PLINK, then gene-based analyses were used for rare variants with the optimized sequence kernel association test (SKAT-O). For genotype–phenotype correlation assessment, regression models were conducted to compare clinical features between the studied groups. Results Three common variants (rs1044006, rs1043997, and rs1043994) showed a nominal protective effect against PD. However, none of these SNPs survived Bonferroni correction. The results in the validation cohort revealed a significant but opposite association between these variants and PD. The gene-based analyses of rare variants showed no significant associations of NOTCH3 with PD. Although we did not find significant associations in the following genotype–phenotype analysis, the higher clinical scores of motor symptoms in NOTCH3-variant carriers were of interest. Conclusion Our results indicated that NOTCH3 gene may not play an important role in the early-onset or familial PD of Chinese population.